Heuristics for evaluating the usability of video game tutorials - Yli-Kovero, Tuomas (My University, 2017)
The usability of video game tutorials can be an important part of a game's player retention and the quality of the game, since tutorials often occur during the very first minutes of gameplay. Having a tool to evaluate the usability of the said tutorials could be useful for game design. To address this problem, this thesis defines a set of heuristics for evaluating the usability of video game tutorials. The new heuristics are a combination of game evaluation heuristics found in the literature and heuristics based on the review of 20 different video games. A total of 27 heuristics were identified. Reviewing of the games was based on existing research in usability, both in productivity software and video games, and applying this to the tutorial experience and thinking about how it could be enhanced based on personal game and usability knowledge and experience. A more extensive testing of these heuristics could provide improvements and benefits both for these heuristics and the development of video game tutorials.